Physical therapists' attitudes are associated with their confidence in and the frequency with which they engage in prescription opioid medication misuse management practices with their patients. A cross–sectional study. Issue 1 (1st December 2022) - Magel, John (Jake); Cochran, Gerald; West, Nancy; Fritz, Julie M.; Bishop, Mark D.; Gordon, Adam J.
Abstract: Background: In the US, prescription opioid medication misuse (POMM) necessitates engagement of physical therapists (PTs). We (1) evaluated the attitudes of (PT) related to their management of patients with POMM and (2) examined the association between these attitudes and PTs confidence in POMM–related management abilities and the frequency with which they engaged in POMM–related management practices. Methods : We conducted a national survey of PTs that included a modified Drug and Drug Problems Perception Questionnaire (DDPPQ). Confidence in POMM–related abilities and the frequency of engaging in POMM–related management practices were measured. Logistic regression evaluated the association between the DDPPQ subscales (role adequacy, role legitimacy, role self–esteem, role support, job satisfaction) and confidence and frequency outcomes. Results : The analysis included 402 respondents. Role adequacy and legitimacy subscales were associated with confidence and frequency outcomes ( p <.05), indicating that more favorable role adequacy and legitimacy attitudes are associated with greater odds of having more confidence in POMM–related management abilities and of engaging in more frequent POMM–related management practices. Conclusions : PTs with a greater sense of preparedness to engage in POMM–related management were more likely to report greater confidence in POMM–related management abilities and engage in POMM–related management practices with greater frequency.